Síntese e avaliação biológica de ésteres derivados do borneol - Aline Teixeira Maciel e Silva (2014)
The terpenes and its derivatives represent compounds of great interest to researchers because of the great potential as a source of new drugs. In this work, esters from the terpene borneol were synthesized using two methodologies (DIC/DMAP and SOCl2). It was also evaluated the microwave irradiation to obtain these compounds, without the use of solvent. It was synthesized 20 borneol esters, among them 18 are not described in the literature. Some of the reactions conducted under microwave irradiation and in the absence of solvent, led to products of rearrangement. The borneol esters had their structures elucidated through spectroscopic and spectrometric methods. The reaction condition in which were used DIC/DMAP and microwave irradiation, in less time produced better yields. The synthesized compounds were subjected to assays to evaluate its activity as antimicrobial, leishmanicidal, cellular antiproliferation and anti-inflammatory. The best results on the antimicrobial assays were found for bornyl 4-methoxybenzoate, bornyl 3,4-dimethoxybenzoate and bornyl 3,4,5-trimethoxybenzoate. It was not observed significative leishmanicidal effect produced by the borneol esters subjected to assay. In relation to the antiproliferative cells assays, bornyl octanoate, bornyl benzoate and bornyl 3,4,5-trimethoxybenzoate showed more promising results, with cytotoxic effects to cell lines of ovarian cancer (OVCAR-3), ovarian-resistant (NCI-ADR/RES), breast (MCF-7), bone marrow (K562) and kidney (786-0). In the anti-inflammatory assays, the bornyl hexanoate, bornyl octanoate, bornyl tetradecanoate, bornyl hexadecanoate, bornyl octadecanoate, bornyl benzoate, bornyl 3,5-dinitrobenzoate and bornyl nicotinate were those that provided better reduction in the edema induced by carrageenin.